2017
DOI: 10.1177/0734282917698302
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the Psychometric Properties of the Revised Children’s Manifest Anxiety Scale–Second Edition Scores Among Chinese Secondary School Students

Abstract: The purpose of this study was to adapt the Revised Children's Manifest Anxiety Scale-Second Edition (RCMAS-2) into Mandarin and to examine its psychometric properties among Chinese adolescents. The participants included 436 Chinese students in Grades 7 to 12 who were administered the Chinese version of the Revised Children's Manifest Anxiety Scale (RCMAS-2-C). Confirmatory factor analyses (CFAs) were performed to examine the factor structure of the RCMAS-2-C. Results indicated a modified four-factor model (Wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 37 publications
3
7
0
Order By: Relevance
“…These were added to the model because of their high modification indices and because their content justified their presence. The correlated errors between the items 23 with 37 and 4 with 10 have already been reported in the study by Zhu and Lowe (2017). Likewise, both pairs of items make up the Inconsistent responding index (Reynolds & Richmond, 2008).…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…These were added to the model because of their high modification indices and because their content justified their presence. The correlated errors between the items 23 with 37 and 4 with 10 have already been reported in the study by Zhu and Lowe (2017). Likewise, both pairs of items make up the Inconsistent responding index (Reynolds & Richmond, 2008).…”
Section: Discussionsupporting
confidence: 62%
“…In this model, the items had factor loadings over .30, which can be seen as a very conservative criterion, however, previous studies have reported similar levels or even under them (Ang et al, 2011;Reynolds & Richmond, 2008;. The modified four-factor model, composed of Physiological anxiety, Worry/Social anxiety, Defensiveness I, and Defensiveness II, has been previously found in the studies by Zhu and Lowe (2017) and Cha et al (2020). However, in studies that reported a structure of three or five factors, the correlation between the factors Worry and Social anxiety was high, with values such as .73 (Reynolds & Richmond, 2008), .74 (Ang et al, 2011), and.77 (Lowe, 2014), justifying the combination of both factors into only one.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…This method provides internal consistency assessments superior to Cronbach's alpha when items are categorical and factor loadings are variable, as was the case with BPQ‐SF items. Like Cronbach's alpha, categorical omega ranges from 0 to 1 and its assessments of internal consistency for published psychometrically‐examined scales includes ranges from .68 to .97 (Roberson & Renshaw, ; Voskuil, Pierce, & Robbins, ; Zhu & Lowe, ). We computed 95% confidence intervals using bias‐corrected and accelerated bootstrapping with 1000 draws.…”
Section: Resultsmentioning
confidence: 99%